We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
83
2
avatar

what is (3x)^2-4y^2 if x=-2 and y=-3

 Oct 9, 2019

Best Answer 

 #2
avatar+19912 
+2

= [3(-2)]2   -  4(-3)2

= 36 - 4(9) = 0

 Oct 9, 2019
 #1
avatar+279 
0

(3x)^2-4y^2 if x = -2 and y = -3

 

(3(-2))^2 - 4(-3)^2

(-6)^2 + 12^2

36 + 144

= 180

 

#SpookySkeleton

CR

 Oct 9, 2019
 #2
avatar+19912 
+2
Best Answer

= [3(-2)]2   -  4(-3)2

= 36 - 4(9) = 0

ElectricPavlov Oct 9, 2019

5 Online Users

avatar